Characterization of goat milk and potentially symbiotic non-fat yogurt - Paz, Noelia Fernanda (2014)
Combining prebiotics and probiotic microorganisms improve quality in the formulation of foods. In this paper, the characteristics of goat milk and symbiotic yogurt were studied. Raw goat milk was analyzed and the skimming process was optimized. For the formulation of a potentially non-fat symbiotic yogurt made with skimmed goat milk, inulin, gelatin, sugar, and Streptococcus salivarius subsp. thermophilus, Lactobacillus delbrueckii subsp. bulgaricus and Lactobacillus casei subsp. rhamnoshus. Chemical characteristics, acceptability, and viability of lactic acid bacteria and probiotic culture were assessed. The protein and fat content of the raw milk was 2.90 and 3.56 g/100 mL, respectively. The optimum skimming process was obtained at 9,800 rpm and 4 °C for 15 minutes. The product formulated had a protein and fat content of 4.04 to 0.04 g/100 mL, good sensory properties, and acceptability of 95%. The lactic bacteria count was 9 × 107 CFU mL - 1, and probiotic culture count was higher than 1 × 106 CFU mL - 1, which guarantees their effect and capacity to survive in the digestive tract and spread in the intestine. The yogurt was stable during the 21 days of storage. Therefore, this study shows that goat milk yogurt is an adequate delivery vehicle of the probiotic culture L. casei and inulin.